Pakistani Students Deserve Better: Why Grammar Translation Method Doesn’t Work for English Learning - Bano, Shaher (UPT Perpustakaan Universitas Jambi, 2025)
This article focuses on the ineffectiveness of the Grammar Translation Method (GTM) for Pakistani students regarding English learning and teaching and the inability to develop essential language skills in the context of globalization. As a product of rote-memorization and teacher-directed approach, GTM continues to encourage the learners to be mere recipients of knowledge, hinders the growth of communication skills, and ignores the factor of linguistic and regional diversity and the needs of students in a multilingual context of Pakistan. The research works under the paradigm of normative research as it evaluates educational practices concerning modern teaching norms. The main points underlined are how the method sharply encourages passive learning, disconnects from context-based experiences, and applies no solution to the linguistic and socio-economic realities of Pakistan. The discussion thus draws attention to the need for adopting a novel pedagogic approach for teaching and learning languages, such as CLT and TBL which are indeed communicative and require group participation and real-life applications. These recommendations are intended to help close the research-practice divide and bring students the skills necessary for success in school and the workplace. Pakistan is capable of transforming the conventional system of ELT by adopting progressive pedagogy to enable learners to acquire the skills and knowledge needed to prevail in the complex multilingual world. This article intends to express that the educationists, the policymakers, and the stakeholders should make a concerted effort to bring change in teaching methodologies of modern languages and should not linger on the old methods for making the future of Pakistani learners brighter and more competitive.